Ultrasound-Guided Paravenous Saphenous Nerve Block for Lower Extremity Abscess Incision and Drainage in a Male Adolescent. Issue 4 (26th April 2023) - Allen, Kelsey W.; Moake, Matthew M.
Abstract: The use of ultrasound-guided regional anesthesia is growing as a modality for analgesia provision within the pediatric emergency department. We present a case in which a paravenous saphenous nerve block was used for anesthesia during incision and drainage of a lower extremity abscess. We further review the technique and literature concerning this straightforward and effective procedure.